2015
DOI: 10.15376/biores.10.2.3265-3276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melamine Allocation Proportion on Chemical Structures and Properties of Melamine-Urea-Formaldehyde Resins

Abstract: Melamine-urea-formaldehyde (MUF) resin was synthesized by adding melamine with a first and second portion of urea, named M1 and M2, respectively. Different allocation proportions of M1:M2 (4:0, 3:1, 2:2, 1:3, and 0:4) were used to develop five MUF (MUF-1, 2, 3, 4, and 5) resins with an F/(U+M) molar ratio of 1.05. The chemical structures, curing behaviors, and cross-section morphology of the resins were characterized. Three-ply plywood was fabricated to evaluate wet shear strength and formaldehyde emission. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
0
17
1
Order By: Relevance
“…The MDF bonded with the UF adhesives with H 3 PO 4 and H 2 SO 4 produced relatively the most methylene linkages and linear methylol content (NHCH 2 OH), which indicate a higher catalytic reactivity in adhesive crosslinking. In this traditional method of producing UF adhesive, H 2 SO 4 has relatively good performance, which is in contrast with previous studies in UMF resin, but it was shown that HCOOH had a better performance than H 2 SO 4 and other catalysts.…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…The MDF bonded with the UF adhesives with H 3 PO 4 and H 2 SO 4 produced relatively the most methylene linkages and linear methylol content (NHCH 2 OH), which indicate a higher catalytic reactivity in adhesive crosslinking. In this traditional method of producing UF adhesive, H 2 SO 4 has relatively good performance, which is in contrast with previous studies in UMF resin, but it was shown that HCOOH had a better performance than H 2 SO 4 and other catalysts.…”
Section: Resultscontrasting
confidence: 92%
“…Many studies have focused on modifying UF resin properties by investigating resin manufacturing parameters, like reaction pH and temperature, different F/U molar ratios, and the use of additives . 13 C‐NMR analysis is a valuable tool for determining the changes in the structures that are synthesized at different temperatures and F/U molar ratios (Figures ).…”
Section: Introductionmentioning
confidence: 99%
“…The other observed peaks of 1130 cm À1 and 1035 cm À1 were assigned to C-O aliphatic ether and methylene bridge (-NCH 2 N-), respectively. 17 The occurrences of the bands conrmed the polymerization of UF resins during a curing process. The obtained results were similar to the other FTIR spectra of cured UF resins with the addition of hardeners.…”
Section: Uf Resin Chemical Compositionmentioning
confidence: 99%
“…Other studies showed that formaldehyde emission can be reduced by over 42% by decreasing the melamine allocation proportion (in the alkaline hydroxymethylation step -M1 and/or alkaline post amino addition step -M2) in three-layer plywood bonded by MUF resin (Luo et al 2015). According to these authors, cheap sepiolite can replace wheat flour as glue mass filler (80%) with MUF resin in plywood production, with an observed reduction of emissions by 7.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the addition of melamine to UF resin allow to obtain the MUF resin, which captures the formaldehyde and decrease its emission (Luo et al 2015). However, melamine addition significantly increases the production cost of panels, thus its use is often limited.…”
Section: Introductionmentioning
confidence: 99%